A novel peptide defined through phage display for therapeutic protein and vector neuronal targeting - James K. Liu; Qingshan Teng; Mary Garrity-Moses; Thais Federici; Diana Tanase; Michael J. Imperiale; Nicholas M. Boulis (Neurobiology of Disease, 2005)
A novel peptide with the binding characteristics of tetanus toxin was identified with phage display, for application in therapeutic protein and vector motor and sensory neuron targeting. A 12mer phage library was biopanned on trisialoganglioside (GT1b) and eluted with the tetanus toxin C fragment (rTTC). Phage ELISAs revealed increases in GT1b binding for the Tet1 and Tet2 phage clones when compared to peptideless phage (PLP). rTTC displaced both Tet1 and Tet2 phage clones from GT1b, and both clones reduced rTTC-GT1b binding. Comparison of Tet1, Tet2, PLP, and the random phage library binding to PC12 and HEK293 cells revealed enhanced cellular binding by Tet1 and Tet2 phage. Tet1 phage binding was selective for neurons. Immunofluorescence also confirmed selective PC12 binding of Tet1 and Tet2 phage. Fluorescein-conjugated synthetic Tet1, but not Tet2, peptide showed strong binding to cultured PC12, primary motor neurons, and dorsal root ganglion (DRG) cells. Synthetic Tet1 bound DRG and motor neurons but not muscle in tissue sections. The enhanced neuronal binding affinity and specificity of Tet1, a novel 12 amino acid peptide, suggests potential utility for targeting neurotherapeutic proteins and viral vectors in the treatment of motor neuron disease, neuropathy, and pain.